(untitled) (Journal of the College of Basic Education, 2022)
Air photos and satellite today have entered many fields and scientific sections because of the wide information available on the surface of the earth. What distinguishes this topic is that it provides information about an area without having to reach or touch it, which makes it superior to the traditional ways of collecting information. The analysis was initially carried out to serve military objectives but was soon used in the civilian sectors, where it was applied in the preparation of topographic maps, soil, geological, agricultural and hydrological fields The interpretation and analysis of aerial and satellite images depends mainly on the user’s experience and ability to identify spatial phenomena and their interpretation, and with the development of science and technology and the entry The era of satellites began to use satellite images to indicate the images taken from the satellites, which reinforced the importance of the subject is that the interpretation of aerial images and satellite images are now using specialized software, so This research came to highlight this issue and its importance by addressing the importance of both aerial and satellite images and distinction between them and then identify the foundations and scientific determinants in the process of analysis and interpretation of visual and classification